HClO‐Activated Fluorescence and Photosensitization from an AIE Nanoprobe for Image‐Guided Bacterial Ablation in Phagocytes. Issue 47 (20th October 2020) - Wu, Min; Wu, Wenbo; Duan, Yukun; Liu, Xingang; Wang, Meng; Phan, Chi Uyen; Qi, Guobin; Tang, Guping; Liu, Bin
Abstract: Bacteria hiding in host phagocytes are difficult to kill, which can cause phagocyte disorders resulting in local and systemic tissue damage. Effective accumulation of activatable photosensitizers (PSs) in phagocytes to realize selective imaging and on‐demand photodynamic ablation of bacteria is of great scientific and practical interests for precise bacteria diagnosis and treatment. Herein, HClO‐activatable theranostic nanoprobes, DTF‐FFP NPs, for image‐guided bacterial ablation in phagocytes are introduced. DTF‐FFP NPs are prepared by nanoprecipitation of an HClO‐responsive near‐infrared molecule FFP and an efficient PS DTF with aggregation‐induced emission characteristic using an amphiphilic polymer Pluronic F127 as the encapsulation matrix. As an energy acceptor, FFP can quench both fluorescence and production of reactive oxygen species (ROS) of DTF, thus eliminating the phototoxicity of DTF‐FFP NPs in normal cells and tissues. Once delivered to the infection sites, DTF‐FFP NPs light up with red fluorescence and efficiently generate ROS owing to the degradation of FFP by the stimulated release of HClO in phagocytes. The selective activation of fluorescence and photosensitization is successfully confirmed by both in vitro and in vivo results, demonstrating the effectiveness and theranostic potential of DTF‐FFP NPs in precise bacterial therapy. Abstract : Aggregation‐induced emission (AIE) nanoprobes with HClO‐activated fluorescence and photosensitization are synthesized for image‐guided bacterial ablation in phagocytes. The fluorescence and photosensitization of the nanoprobes are selectively activated at a bacterial infection site, which facilitates the precise diagnosis and therapy for bacterial infection with no obvious side effects.